A Model of Soviet-Type Economic Planning: Reply - Manove, Michael (American Economic Review, 1972)
J. M. Montias is primarily concerned with the effectiveness of the iteration, the only completely decentralized planning procedure described in my model. He has two main points. First, he shows that when production in every sector is centrally planned, the addition of a iteration to the planning procedure may actually increase supplydemand imbalances. Secondly, he argues that given the existence of capacity limitations, the retrospective iteration is likely either to generate gross outputs in excess of these limits or to generate an inferior bill of final demands in the course of the plan execution. Both of Montias's points have very important implications for the interpretation of the model, and I would like to comment on them.